1985
DOI: 10.1149/1.2113606
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Properties of Nickel in the Temperature Range 1073–1500 K

Abstract: OXYGEN SummaryIncremental growth rates in dry oxygen of oxides on silicon in the same furnace are found to differ by more than two. These rates are directly related to the index of refraction of the initial oxide film and thus to the original growth temperature. Therefore, there seems to be a change in diffusion rate because of a change in the oxide structure with growth temperature. This structure factor when added to the activation energy for the diffusion of oxygen through fused quartz could account for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 5 publications
0
10
1
1
Order By: Relevance
“…Fueki and Wagner (4) observed that the value of n was 8 at~temperatures from 1273 to 1373 K, and decreased to 6 at 1463 K and to 3 at 1673 K. They evaluated the diffusivity as a function of oxygen partial pressure from the tangent of the plot of kp vs. log (Po2), and concluded that the diffusivity was independent of oxygen partial pressure below ~0.1 Pa and increased as the oxygen pressure rose above ~0.1 Pa. The value of n varied from 5.6 at 1273 K to 3.5 at 1673 K. On the other hand, Godlewski et al (5) studied the high temperature oxidation of nickel in the temperature range of 1273 -1633 K, at oxygen partial pressures between 1.7 x l0 s and 1.0 x 10 ,~ Pa. Their value of n decreased from 10 to 4.2, with increasing temperature, and they concluded that the inward diffusion of oxygen through the oxide grain boundaries was significant below 1381 K, and that this increased the value of n. Recently, Elrefaie et al (6) found the value of * Electrochemical Society Active Member. n to be around 6 in the oxidation experiments, at temperatures between 1073 and 1500 K, and at oxygen partial pressures of 10 ~ -10 ' Pa.…”
mentioning
confidence: 99%
“…Fueki and Wagner (4) observed that the value of n was 8 at~temperatures from 1273 to 1373 K, and decreased to 6 at 1463 K and to 3 at 1673 K. They evaluated the diffusivity as a function of oxygen partial pressure from the tangent of the plot of kp vs. log (Po2), and concluded that the diffusivity was independent of oxygen partial pressure below ~0.1 Pa and increased as the oxygen pressure rose above ~0.1 Pa. The value of n varied from 5.6 at 1273 K to 3.5 at 1673 K. On the other hand, Godlewski et al (5) studied the high temperature oxidation of nickel in the temperature range of 1273 -1633 K, at oxygen partial pressures between 1.7 x l0 s and 1.0 x 10 ,~ Pa. Their value of n decreased from 10 to 4.2, with increasing temperature, and they concluded that the inward diffusion of oxygen through the oxide grain boundaries was significant below 1381 K, and that this increased the value of n. Recently, Elrefaie et al (6) found the value of * Electrochemical Society Active Member. n to be around 6 in the oxidation experiments, at temperatures between 1073 and 1500 K, and at oxygen partial pressures of 10 ~ -10 ' Pa.…”
mentioning
confidence: 99%
“…The surrounding region of smaller (~10 µm) grained material is more typical, in appearance, of oxide films seen in the oxidation literature (Elrefaie et al. , 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The molar volumes of the oxides are V(CrO 1.5 ) = V(BO m ) = 14.59 cm 3 /mol and V(AlO 1.5 ) = V(CO l ) = 12.86 cm 3 /mol, while that of the alloys has been set equal to the value of pure nickel (6.594 cm 3 /mol). The rate constant for the oxidation of pure nickel at 1200°C used by Nesbitt, k c (NiO), is equal to 5.4 Â 10 11 cm 2 /s, 22 but the value used here is that calculated from the data reported by Elrefaie et al, 26 which, after conversion in terms of thickness of metal consumed, becomes equal to k c (NiO) = 1.56 Â 10 )10 cm 2 /s.…”
Section: Single Front Of Internal Oxidationmentioning
confidence: 98%